Avaliação da germinação e crescimento inicial de espécies florestais arbóreas frente exposição a pesticidas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The use of pesticides is advancing fastly in the world, partly, justified by population growth. However, these substances are often used indiscriminately, above the recommended doses, leading to ground contamination, surface and groundwater, and consequently, the environment damage, affecting non-target organisms. It is possible to estimate the harmful effects of pesticides on organisms using ecotoxicology support, which is an area of study that uses different methodologies through bioassays with organisms sensitive tests to the toxic substance effect tested. The aim of this study is to verify the response of botanical species Hymenolobium petraeum Ducke and Enterolobium schomburgkii Benth exposed to concentrations of cypermethrin, atrazine, glyphosate and 2,4-D pesticides in seed germination and in the early growth phase. The concentrations used were ¼, ½, recommended average concentration, 2x and 4x. The seeds were collected and submitted to pre-experiment treatment of disinfection and chemical scarification. The study was developed in a controlled environment and divided into two stages: test I - morphometric evaluation and seeds exhibition to different pesticides concentration, where the germination speed index - GSI, germination percentage - G (%) and final mortality - FM (%) of seeds were evaluated; and test II - evaluation of variables in seedlings during 30 days exhibiting to pesticide concentration, where stem length -SL, root length -RL, collar diameter -CD, air part dry material mass – APDM, root dry material mass – RDM, total dry material mass – TDM were estimated. In addition, the mean effective concentration (CE50) values were estimated based on the percentage of test organisms mortality. In test I, the average results for width, thickness and length of seeds were observed, which were 7.48, 1.70 and 13.54 mm for H. petraeum and 4.31, 2.43 and 7.51 mm for E schomburgkii, respectively. The weight of 1000 seeds was 155.79 g for H. petraeum and 64.6 g for E. schomburgkii. In assay I, the CE50 for H. petraeum was 2.34 mg/L for glyphosate and 1.49 mg/L for 2-4-D, while for E. schomburgkii the CE50 was 6.38 mg/L to 2,4-D. In assay II, for H. petraeum and E. schomburgkii the CE50s were respectively 26.72 and 9.66 mg/L for atrazine, 11.96 and 20.20 mg/L for glyphosate and 5.34 and 9.67 mg/L for 2.4D. The pesticide concentration can affect non-target organisms such as Hymenolobium petraeum and Enterolobium schomburgkiit delaying and inhibiting GSI and G (%) and, causing MF (%) of organisms mainly affected by atrazine, glyphosate and more severely by 2,4-D formulations. The test II showed that growth variables as plant dry material mass were the most affected by pesticides concentration studied.
Keywords: Espécies florestais; Substâncias químicas; Ensaios ecotoxicológicos